If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5v + -7)(3 + -1v) = 0 Reorder the terms: (-7 + 5v)(3 + -1v) = 0 Multiply (-7 + 5v) * (3 + -1v) (-7(3 + -1v) + 5v * (3 + -1v)) = 0 ((3 * -7 + -1v * -7) + 5v * (3 + -1v)) = 0 ((-21 + 7v) + 5v * (3 + -1v)) = 0 (-21 + 7v + (3 * 5v + -1v * 5v)) = 0 (-21 + 7v + (15v + -5v2)) = 0 Combine like terms: 7v + 15v = 22v (-21 + 22v + -5v2) = 0 Solving -21 + 22v + -5v2 = 0 Solving for variable 'v'. Factor a trinomial. (-3 + v)(7 + -5v) = 0Subproblem 1
Set the factor '(-3 + v)' equal to zero and attempt to solve: Simplifying -3 + v = 0 Solving -3 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + v = 0 + 3 Combine like terms: -3 + 3 = 0 0 + v = 0 + 3 v = 0 + 3 Combine like terms: 0 + 3 = 3 v = 3 Simplifying v = 3Subproblem 2
Set the factor '(7 + -5v)' equal to zero and attempt to solve: Simplifying 7 + -5v = 0 Solving 7 + -5v = 0 Move all terms containing v to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5v = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5v = 0 + -7 -5v = 0 + -7 Combine like terms: 0 + -7 = -7 -5v = -7 Divide each side by '-5'. v = 1.4 Simplifying v = 1.4Solution
v = {3, 1.4}
| 4x+4=5x+10 | | (2n-3)(n+4)=0 | | 6c-6-2c-5-3c+7= | | 8+(x+5)= | | x^3-10x^2+13x+74=0 | | 5b+3(3b+4)=-24+2b | | x*2-x=20 | | v=(50-2x)(50-2x)(x) | | y=5*cos*2x+11 | | (5z+6)(4-z)=0 | | q-1=5q+3q-8 | | 0.16=-0.4+0.7x | | 8.5+3.4= | | (4z+7)(5+z)=0 | | 1.2=-1.4+20x | | -9x+4y=7 | | 5x-y=14.9 | | 5x+7=-6+2x+19 | | 4x+y-4=0 | | 4x-9=-3x+5 | | 3(4x-2)+5x=30x | | S^2+2s= | | -4x-9=2x+9 | | 2=2.2x-15 | | 5-11p=17 | | 18x-12y+23=0 | | 8.5+3(9-5)= | | -4(7)-2y=-10 | | 3x+(-5x)= | | 55(6x-6)(7x+1)= | | -10x-10(-10)=20 | | y^2+4x+10y+29=0 |